Assessing Workplace Readiness of Vocational School Students for Industry 5.0: A Skills Gap Analysis - Rahayu, Sri; Meirawan, Danny; Ghinaya, Zahra; Gandra, Mario (Universitas Negeri Yogyakarta, 2025)
Background: The fast-paced growth of the global landscape has triggered significant transformations in various sectors, including education and the workforce. As the world enters the era of Industrial Revolution 5.0, which emphasizes sustainability and human-technology collaboration, it becomes critical for vocational high school (SMK) graduates to possess job skills that align with modern industry demands. However, a persistent skills gap remains between what vocational education delivers and what industries require. Methods: This study aims to analyse the employability level of vocational high school students in meeting industry demands during the Industrial Revolution 5.0. A quantitative approach was employed using an online survey distributed to 450 vocational students and 40 industry representatives across various sectors in Indonesia. The survey instrument focused on two main job skill dimensions: problem-solving practices and planning and organizing activities. Descriptive statistical analysis (frequency distributions, means, and standard deviations) was conducted, followed by inferential analysis using a t-test to compare students' self-assessments with industry evaluations of job readiness. Results: The findings revealed that vocational students' skills are currently at a moderate level and have not yet fully met industry expectations. A statistically significant gap was found between student perceptions and industry assessments, indicating a misalignment in readiness levels. Conclusion: These results highlight a critical employability gap that must be addressed to ensure vocational graduates are better prepared for the evolving workforce. Strengthened collaboration between vocational education institutions and industry is essential. Joint efforts should focus on establishing shared competency standards, enhancing industry-based training programs, and increasing industry participation in curriculum development to improve the alignment between education outcomes and labour market needs.